Nano‐Biomedicine based on Liquid Metal Particles and Allied Materials. Issue 4 (8th April 2021) - Sun, Xuyang; Yuan, Bo; Wang, Hongzhang; Fan, Linlin; Duan, Minghui; Wang, Xuelin; Guo, Rui; Liu, Jing
Abstract : Nano‐Biomedicine In article number 2000086, Xuyang Sun, Jing Liu, and co‐workers outline broad biomedical applications of liquid metal particles based on the unique merits of liquid metals, including shape‐transformation, easy fabrication, excellent biocompatibility, and diverse stimuli‐responsive characterizations. With the excellent fluidic nature, liquid metal particles can perform diverse biomedical tasks from diagnostics to therapeutics, such as DNA detection, drug delivery, photothermal therapy, enhanced bioheat transfer, and mechanical destruction of tumors.